2012
DOI: 10.1089/ars.2010.3766
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 3 Is a Key Molecule Regulating Adipocyte Oxidative Stress, Mitochondrial Biogenesis, and Adipokine Expression

Abstract: Aims: Increased oxidative stress and mitochondrial dysfunction in obese adipocytes contribute to adipokine dysregulation, inflammation, and insulin resistance. Results: Through an advanced proteomic analysis, we found that peroxiredoxin 3 (Prx3), a thioredoxin-dependent mitochondrial peroxidase, is highly expressed in 3T3-L1 adipocytes compared to preadipocytes. Interestingly, in obese db/db mice and human subjects, adipose Prx3 levels were significantly decreased, indicating its association with obesity. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 42 publications
0
109
0
1
Order By: Relevance
“…Collectively, these data suggest that early increases in S-glutathionylation of Fas (Fas-SSG) occurred independently of changes in Grx1 content, caspase-3 activity, or efflux of GSH. We next examined whether FasL altered the redox status in specific subcellular compartments by monitoring overoxidation of Prx1, Prx3, or Prx4, which are localized in the cytosol, mitochondria, and endoplasmic reticulum (ER), respectively (21,36,44). Immunoprecipitation (IP) of Prx1, Prx3, or Prx4 and subsequent Western blotting for overoxidized forms of Prx (PrxSO 3 ) revealed rapid overoxidation of Prx4, which occurred within 10 min following ligation of Fas and was sustained for at least 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data suggest that early increases in S-glutathionylation of Fas (Fas-SSG) occurred independently of changes in Grx1 content, caspase-3 activity, or efflux of GSH. We next examined whether FasL altered the redox status in specific subcellular compartments by monitoring overoxidation of Prx1, Prx3, or Prx4, which are localized in the cytosol, mitochondria, and endoplasmic reticulum (ER), respectively (21,36,44). Immunoprecipitation (IP) of Prx1, Prx3, or Prx4 and subsequent Western blotting for overoxidized forms of Prx (PrxSO 3 ) revealed rapid overoxidation of Prx4, which occurred within 10 min following ligation of Fas and was sustained for at least 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…As antioxidant defense system, Peroxiredoxin (Prx) 3, Prx5, superoxide dismutase 2, and thioredoxin 2 eliminates ROS produced in mitochondria [30,31] . Knockout (KO) of Prx3 mice result in induction of oxidative damage [32] , KO of thioredoxin 2 mice showed an embryonic lethal phenotype [33] and KO of superoxide dismutase 2 mice die within 3 wk of birth because of mitochondrial into the matrix of mitochondria. This mitochondrial permeability transition (MPT) leads to osmotic swelling of the mitochondrial matrix and dissipation of the ∆ Ψm [38,39] , and eventually cell death occurs due to mitochondrial outer membrane permeabilization [40] .…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
“…PRDX3 was identified as a member of the peroxiredoxin protein family (Prx), which acts as a cellular defense system against oxidative stress and whose catalytic activity and protein sequences are different from those of other antioxidants (Dietz et al, 2002). Overexpression of PRDX3 has been reported in mesothelioma, HCC, breast cancer, and ovarian cancer, suggesting that it may be involved in tumorigenesis and cancer progression (Huh et al, 2012). Recently, Qiao et al identified PRDX3 using differential tissue proteome analysis as a novel molecular marker for HCC progression (Qiao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%